QAShQADAYO VILOYATI AHOLI MANZILGOHLARI ShAKLLANIShI VA RIVOJLANIShINING NAZARIY ASOSLARI - Qurbonov, P.R.; Qo‘ldosheva, G.M. (SCIENCE and SOCIETY, 2025)
In recent years, the rapid growth of the population in our Republic has increased the demand for settlements. The development of settlements, especially in parts of the oasis surrounded by desert, is a rather complicated process. This article studies the geographical location of the settlements of the Kashkadarya oasis. The article presents observations on the specific geographical location, population, history of formation, and settlements of the settlements in the region.
Keywords: population settlements; cities; districts; villages; geographical location; ecological situation; industry; development